2021
DOI: 10.1088/1755-1315/667/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pH and cooking losses of chicken meat due to the use of different percentages of turmeric flour

Abstract: The use of turmeric as an active compound for preservatives is widely used because it is simple, inexpensive, and easy to find. To prevent the losses of quality and damage to the meat, processing and preservation is required. The purpose of this study was to determine the effect of using different percentages of turmeric flour on the pH and cooking losses of chicken meat. This study used 2.2 kg Broiler chicken breast and 214.5 g turmeric flour. The research design used was a completely randomized design consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
5
1
Order By: Relevance
“…The authors obtained higher values of L* (55.34), a* (12.49) and b* (6.78) for the breast muscles of broiler hens from broiler breeder flocks at 75 weeks of age compared to the results of our study (L*-45.1, a*-5.8, b*-3.8, respectively). In contrast, a* and b* saturation values of the leg muscles in our study were higher than those reported by Choe and Kim [35], while the L* color saturation (47.45) was lower in our study (LM-36.4). The results obtained by the latter authors were influenced by the genotype of the birds, as the pH 24 of the leg muscles (OBH-6.3) was at a comparable level to the results obtained in our study (pH LM-6.37).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The authors obtained higher values of L* (55.34), a* (12.49) and b* (6.78) for the breast muscles of broiler hens from broiler breeder flocks at 75 weeks of age compared to the results of our study (L*-45.1, a*-5.8, b*-3.8, respectively). In contrast, a* and b* saturation values of the leg muscles in our study were higher than those reported by Choe and Kim [35], while the L* color saturation (47.45) was lower in our study (LM-36.4). The results obtained by the latter authors were influenced by the genotype of the birds, as the pH 24 of the leg muscles (OBH-6.3) was at a comparable level to the results obtained in our study (pH LM-6.37).…”
Section: Resultscontrasting
confidence: 99%
“…In addition to the aforementioned physicochemical characteristics, cooking loss is of great importance in assessing the suitability of meat. According to Abubakar et al [35], meat with high cooking loss has poorer quality traits owing to cooking leading to the loss of nutritional components. In our study, the breast muscles of Ross 308 showed higher cooking loss, while Cobb 500 birds had higher cooking loss in the leg muscles (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooking losses in this study were lower than those found in some previous studies on Cobb 500 broiler (25.3% and 24.7%) and on commercial chicken hybrid (21.05% and 26.23%) breast muscles ( Petracci et al, 2013 ; Benamirouche et al, 2020 ). Cooking loss is one of the important determinants of meat quality, because it is related to the amount of water lost and nutrients that dissolve in water due to the influence of the cooking process ( Abubakar et al, 2021 ). According to these authors, meat with low cooking losses has better physical quality when compared to meats that have higher cooking losses, because the loss of nutrients during the cooking process is less.…”
Section: Resultsmentioning
confidence: 99%
“…These results are closely aligned with our findings. Contrastingly, Abubakar et al (2021) reported that the pH of meat significantly differed among turmeric treated groups compared with control. The pH of meat is a crucial indication for the acceptability of meat to the consumer.…”
Section: Meat Qualitymentioning
confidence: 83%